The Limits of Consent Sexual Assault and Affirmative Consent - Featherstone, Lisa (Palgrave Socio-Legal Studies, 2024)
This open access book examines the ways that consent operates in contemporary culture, suggesting it is a useful starting point to respectful relationships. This work, however, seeks to delve deeper, into the more complicated aspects of sexual consent. It examines the ways meaningful consent is difficult, if not impossible, in relationships that involve intimate partner violence or family violence. It considers the way vulnerable communities need access to information on consent. It highlights the difficulties of consent and reproductive rights, including the use (and abuse) of contraception and abortion. Finally, it considers the ways that young women are reshaping narratives of sexual assault and consent, as active agents both online and offline. Though this work considers victimisation, it also pays careful attention to the ways vulnerable groups take up their rights and understand and practice consent in meaningful ways.